Multilayer coupled ring resonator filter / Nurul Fazleena Muhamad Arif - Muhamad Arif, Nurul Fazleena (2011)
The purpose of this project is to design and simulation of multilayer microstrip bandpass filter based on coupled ring resonator. This filter is presented by cascading a ring resonator for a results of a wider bandwidth used for wideband applications. This filter is centered at 2.58 GHz with fractional bandwidth of 7.13% from 2.4752 GHz to 2.6589 GHz on 0.75 mm thick Rogers RO3003 substrate with dielectric constant of 3, loss tangent of 0.0013 and 0.035 copper thickness. Multilayer filter technology used to meet the challenges of meeting size, performances and cost requirements. The Computer Simulation Technology (CST) is used to simulate filter responses. Results from the simulation filter involving return loss, Sn and insertion loss, S21 are revealed through this project. The value of Sn and S21 are -27.299 dB and -0.5246 dB respectively at the operated center frequency. The proposed filter has the advantages of broader fractional bandwidth greater than 5%, small dimensions and sharper rejection.